The clinical spectrum of a nonsense mutation in KAT6A: a case report. Issue 12 (December 2022) - Wang, Dongbo; He, Jun; Li, Xueyi; Yan, Shuyuan; Pan, Linglin; Wang, Tuanmei; Zhou, Liangrong; Liu, Jiyang; Peng, Xiangwen
KAT6A syndrome is an autosomal dominant genetic disorder associated with intellectual disability due to mutations in the lysine acetyltransferase 6A ( KAT6A ) gene. There are some differences in phenotype between KAT6A gene variants. This current case report describes a 1-month-old male infant that had a nonsense mutation in the KAT6A gene. Neither of his parents had the mutation. The proband had feeding difficulties and a physical examination revealed the following: moderate dysphagia, hypoplastic laryngeal cartilage, poor audio-visual response, poor head-up ability, no active grasping awareness, microcephaly, high arched palate and he was significantly behind other children of the same age. Echocardiography showed that the foramen ovale was not closed. He was diagnosed with atrial septal defect (ASD) when 2 years old. The patient received ASD repair at 32 months of age. Head colour Doppler ultrasonography and brain magnetic resonance imaging showed cysts in the right ventricle and choroid plexus, which returned to normal at 2 years of age. This current case demonstrates that immediate surgery should be considered in newborns with KAT6A syndrome presenting with a heart malformation. A new KAT6A syndrome phenotype is described in this current case report, which requires early diagnosis and treatment.